Coagulation process optimization as dissolved air flotation pre-treatment for the removal of natural organic matter treating Ottawa river water (Revista de Diavulgación L'esprit Ingénieux, 2021)
Natural organic matter (NOM) impacts water quality by adding color, odor, and flavor in water treatment plants (WTPs). Turbidity and NOM removals in WTPs are conducted using coagulation, flocculation, and clarification processes. The objective of this research was to evaluate different coagulant doses at different target pH to find an optimum combination of pH and coagulant dose for removing NOM using dissolved air flotation (DAF) as a clarification process. The results showed that the optimal dose for NOM reduction measured as dissolved organic carbon (COD), ultraviolet absorbance at 254 nm (UV-254) and true color was 30 mg/L as Al2O3 (2.73 mg Al/L) for a target pH of 6.0. However, the best reduction of the specific UV absorption (SUVA) had a target pH of 5.0 with the same optimal coagulant dose of 30 mg/L as Al2O3 (2.73 mg Al/L).
Keywords: Natural organic matter; Coagulation; Flocculation; Dissolved air flotation